PENGARUH GAYA KEPEMIMPINAN KEPALA MADRASAH, SUPERVISI AKADEMIK DAN BUDAYA KERJA TERHADAP PROFESIONALISME GURU DI MADRASAH ALIYAH SWASTA SE-KABUPATEN BATANG - Muchsinin; Nor Miyono; Rasiman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The professionalism of teachers in private Madrasah Aliyah (MA) in Batang Regency remains relatively low, particularly in the dimensions of evaluating learning outcomes, planning in academic supervision, directive transformational leadership style, and innovation and risk-taking in work culture. This study aims to examine: (1) the significant influence of school principal leadership style on teacher professionalism, (2) the significant influence of academic supervision on teacher professionalism, (3) the significant influence of work culture on teacher professionalism, and (4) the simultaneous influence of school principal leadership style, academic supervision, and work culture on teacher professionalism in private Madrasah Aliyah in Batang Regency. This quantitative research involved a population of 210 teachers and a sample of 137 respondents selected through random sampling. Data collection was conducted using questionnaires and documentation, and the data were analyzed using simple and multiple regression with SPSS version 26. The results indicate that the school principal leadership style, academic supervision, and work culture each have a positive and significant influence on teacher professionalism. Simultaneously, these three variables also significantly influence teacher professionalism, contributing 58.2% to its variability, while the remaining 41.8% is influenced by other factors. This study recommends that school principals enhance two-way communication with teachers, optimize supervision planning, and conduct reflection and evaluation of supervision activities. Teachers are advised to be more open to constructive criticism, innovate, and continually improve their competencies to enhance professionalism in line with current educational demands.